Iowa Birdline update, February 1, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email for the Iowa Birdline update for February 1, 1993. Highlights of the update include sightings of the continued presence of Iceland Gulls, two Townsend's Solitaires, a Long-tailed Duck and two Trumpeter Swans. Also included are handwritten notes for the next week's update with sightings of a Northern Saw-whet Owl and two Long-eared Owls at Big Creek State Park, and an additional Northern Saw-whet Owl sighted at Ledges State Park. Epson - sheet feed/flatbed